2021
DOI: 10.3233/adr-210006
|View full text |Cite
|
Sign up to set email alerts
|

Can Porphyromonas gingivalis Contribute to Alzheimer’s Disease Already at the Stage of Gingivitis?

Abstract: Alzheimer’s disease (AD) has been associated with periodontitis, which starts as gingivitis. Similar to periodontitis, gingivitis bacteria, bacterial products, and inflammatory mediators can travel to the brain via the blood stream and promote brain inflammation. Periodontal pathogens such as Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, both associated with AD, have been found in dental plaque of children already at the age of 3. It is suggested that these bacteria during long-term expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This is because periodontitis can cause a secretion of bacterial pathogens, such as LPS or peptidoglycans, which have been considered as modifiable risk factors for AD [ 136 ]. As previously indicated in this work, periodontitis has been associated with increased risk of dementia through the mechanisms of systemic inflammation [ 117 , 137 , 138 ]. Another study corroborates the fact that oral microbiota may influence the risk of AD through systemic access to the brain of imbalanced oral microbiota strains and hypothesizes the relationship that AD neuropathology may establish with periodontitis through this mechanism [ 139 ].…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…This is because periodontitis can cause a secretion of bacterial pathogens, such as LPS or peptidoglycans, which have been considered as modifiable risk factors for AD [ 136 ]. As previously indicated in this work, periodontitis has been associated with increased risk of dementia through the mechanisms of systemic inflammation [ 117 , 137 , 138 ]. Another study corroborates the fact that oral microbiota may influence the risk of AD through systemic access to the brain of imbalanced oral microbiota strains and hypothesizes the relationship that AD neuropathology may establish with periodontitis through this mechanism [ 139 ].…”
Section: Resultsmentioning
confidence: 76%
“…It is known that oral status may be an important factor for general health and a diverse and well-developed microbiota has been associated with overall well-being. Thus, prevention of oral pathologies and inhibition of the protease of P. gingivalis or other bacteria associated with periodontitis and AD, such as A. actinomycetemcomitans , Actinomycetales and Prevotella [ 137 , 139 ], T. forsythia , E. coli , Chlamydiapneumonia and F. nucleatum may help to reduce the current neurodegenerative burden [ 152 ], an extremely compelling hypothesis that requires of further investigation. It has been presupposed that the oral microbiota remains in the oral cavity and does not have the ability to preferentially reach the intestine or other body sites.…”
Section: Resultsmentioning
confidence: 99%
“…The association of specific molecules between PD and AD [40], a direct possible role of P gingivalis [41] crossing blood-brain barrier [42], and leading to induced AD like condition in diabetic mice [43], are recently documented. The cognitive decline in young people with PD [44] and dementia/AD signs in earliest stage of PD (gingivitis) [45] are also being studied.…”
Section: Discussionmentioning
confidence: 99%
“…An accumulating body of evidence has shown that untreated periodontitis is associated with several systemic conditions such as diabetes, rheumatoid arthritis, adverse pregnancy outcomes, renal diseases, and coronary heart disease (CHD), including myocardial infarction (MI) and angina pectoris (Potempa et al, 2017;Deschamps-Lenhardt et al, 2019;Joshi et al, 2019;Preshaw & Bissett, 2019;Nguyen et al, 2020;Olsen, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is characterized by chronic inflammation of the tooth‐supporting structures, caused by dysbiotic subgingival microbiota and worsened by risk factors such as smoking and uncontrolled diabetes. An accumulating body of evidence has shown that untreated periodontitis is associated with several systemic conditions such as diabetes, rheumatoid arthritis, adverse pregnancy outcomes, renal diseases, and coronary heart disease (CHD), including myocardial infarction (MI) and angina pectoris (Potempa et al, 2017; Deschamps‐Lenhardt et al, 2019; Joshi et al, 2019; Preshaw & Bissett, 2019; Nguyen et al, 2020; Olsen, 2021).…”
Section: Introductionmentioning
confidence: 99%